Panx3 links body mass index and tumorigenesis in a genetically heterogeneous mouse model of carcinogen-induced cancer. Issue 1 (December 2016) - Halliwill, Kyle; Quigley, David; Kang, Hio; Del Rosario, Reyno; Ginzinger, David; Balmain, Allan
Abstract Background Body mass index (BMI) has been implicated as a primary factor influencing cancer development. However, understanding the relationship between these two complex traits has been confounded by both environmental and genetic heterogeneity. Methods In order to gain insight into the genetic factors linking BMI and cancer, we performed chemical carcinogenesis on a genetically heterogeneous cohort of interspecific backcross mice ((Mus Spretus × FVB/N) F1 × FVB/N). Using this cohort, we performed quantitative trait loci (QTL) analysis to identify regions linked to BMI. We then performed an integrated analysis incorporating gene expression, sequence comparison between strains, and gene expression network analysis to identify candidate genes influencing both tumor development and BMI. Results Analysis of QTL linked to tumorigenesis and BMI identified several loci associated with both phenotypes. Exploring these loci in greater detail revealed a novel relationship between the Pannexin 3 gene (Panx3 ) and both BMI and tumorigenesis.Panx3 is positively associated with BMI and is strongly tied to a lipid metabolism gene expression network. Pre-treatmentPanx3 gene expression levels in normal skin are associated with tumor susceptibility and inhibition of Panx function strongly influences inflammation. Conclusions These studies have identified several genetic loci that influence both BMI and carcinogenesis and implicatePanx3 as a candidate gene that links these phenotypes through its effects on inflammation and lipid metabolism.